International technology transfer examined at technology component level a case study in China - Lan, Ping (Technovation)
This paper develops the concept of a 'technology ball' and applies this to the case of foreign direct investment (FDI)-based technology transfer in Dalian City, Northeast China. The results indicate that current technology transfer is dominated by hardware transplantation, while the technology associated with innovation skills is rarely transferred. Because the technology value of FDI is low, the technology ball itself is small and important policy changes are necessary in order to facilitate movement in the ball, that is to stimulate technology transfer through FDI.